Research Progress of Traditional Chinese and Western Medicine on Precancerous Lesions of Gastric Cancer - Yi, Juanyu; Qiao, Huixia (Journal of Contemporary Medical Practice, 2026)
Precancerous lesions of gastric cancer (PLGC) are pathological changes arising from multiple pathogenic factors, characterized by intestinal metaplasia, dysplasia, or intraepithelial neoplasia superimposed on chronic atrophic gastritis (CAG). They represent a critical transitional stage from normal gastric mucosa to gastric cancer. Currently, modern medicine has made certain progress in elucidating the pathogenic factors and pathogenesis of PLGC. Treatment primarily involves eradication of Helicobacter pylori (Hp), acid suppression and gastric mucosal protection, supplementation with vitamins and folic acid, and endoscopic surgical procedures; however, it remains difficult to reverse the pathological alterations. In recent years, traditional Chinese medicine (TCM), through syndrome differentiation and treatment as well as comprehensive intervention, has achieved relatively satisfactory therapeutic efficacy in managing PLGC, demonstrating its potential advantages. This article reviews and summarizes the research on the diagnosis and treatment of PLGC with traditional Chinese and Western medicine in recent years, aiming to provide a reference for further promoting the clinical application and research of TCM in this field.